Technical Training Plan in Artistic Swimming for Children: A Comprehensive Planning Approach (RIAF. International Journal of Physical Activity, 2026)
AbstractIntroduction: Technical training is essential in artistic swimming for competitive performance, focusing on positions, figures, and routines. Although previous research exists on biological and methodological aspects, there is a lack of comprehensive approaches that include sociological and psychological dimensions, as well as inconsistent didactic planning in regulatory documents.Objective: To develop a technical training plan for young artistic swimmers (11-12 years old) from a comprehensive sports perspective.Methods: A qualitative methodology was used. The theoretical methods included analytical-synthetic methods for reviewing the literature and systemic-structural-functional methods for conceiving the plan as an interrelated system. The main empirical method was the documentary analysis of the Comprehensive Athlete Preparation Program (PIPD) and existing training plans, identifying inconsistencies in content, exercises, and load dosage. The proposed plan was based on Matveev's (1983) cyclical periodization model, adapted to the U12 category with a specific distribution of periods (80% preparatory, 20% competitive) and stages, 4:1 mesocycles, and microcycles. Training frequencies, work time, volume and intensity dosages (with a margin of tolerance), and evaluation controls were defined, employing sensory-perceptual, verbal, and practical methods. Results: The proposal restructured the technical content load, integrating psychomotor, sensory-perceptual, volitional, motivational, sociological, and psychological dimensions, in line with theories such as Vygotsky's. This allowed for overcoming the inconsistencies of the PIPD (Professional Development Plan) and the deficiencies in didactic planning, ensuring a logical progression of technical elements. The application of Hans Selye's Law of Bioadaptation and Matveev's principles ensured a gradual and undulating progression of training loads, essential for adaptation. The plan provides a detailed methodological guide, facilitating the organization and application of technical training for functional improvement and holistic development.Conclusions: A comprehensive technical training plan for young artistic swimmers was successfully developed, incorporating sociological, psychological, and pedagogical aspects. This proposal offers a new way to periodize and structure training loads, serving as a valuable tool for coaches and promoting holistic development and athletic performance in artistic swimming.
Keywords: Aquatic sports; sports planning; technical training; young swimmers